Pengaruh Management Laba, ROE, dan Ukuran Perusahaan Terhadap Dividen Payout Ratio Pada Perusahaan Jasa Yang Go Public di Indonesia - Yosy arisandy (Al-Intaj : Jurnal Ekonomi dan Perbankan Syariah, 2015)
This study is performed to effect of earnings management, roe and company size of dividend payout ratio. The object of the research was service company (telecommunications, transportation, hospitality, tour and travel) which go public in indonesia. This study adopted research by Ahmed Arif (2011) with some modification. The researchers have taken the data of listed service companies for the year 2008 to 2010. the company that represents their financial report over period 2008 – 2010. The researchers have measured the dividend policy by using dividend payout ratio while Modified Cross Sectional Jones Model (1995) has been employed to measure the earnings management. This study reveals that based on the results of regression analysis and F test can be seen that there is positive and significant influence between earnings management, the variable return on equity (ROE) and the size of the company's dividend payout ratio, with a significance level of less than 5%; Based on the results of the t-test, it is known that there are partially positive and significant influence among the variables return on equity (ROE) and the size of the company's dividend payout ratio. While earnings management has a negative effect and no significant effect on dividend payout ratio, the significance level of 5%.